2007
DOI: 10.2215/cjn.03781106
|View full text |Cite
|
Sign up to set email alerts
|

Subdural Hematomas in Chronic Dialysis Patients

Abstract: Background and Objectives: Subdural hematoma is a known complication of long-term hemodialysis. Design, Setting, Participants, and Measurements: The US Renal Data System was used to determine the occurrence rate of nontraumatic subdural hematoma in long-term dialysis patients and to evaluate time trends.Results: The occurrence rate of subdural hematoma in long-term dialysis patients is 10 times higher than that of the general population. From 1991 to 2002, the occurrence rate of subdural hematoma in hemodialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
33
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 19 publications
6
33
0
2
Order By: Relevance
“…2 the US Renal Data System reported a 10-fold increase in subdural hemorrhages in dialysis patients (although their medication was not specified) when compared with nondialysis patients, 43 whereas a review of 28 studies of warfarin use in dialysis patients suggested its use doubled the risk for major bleeding. 44 Treated hypertension, 18 -20,45,46 cerebrovascular disease, 23 ischemic stroke, 21,47 serious heart disease, 23 renal insufficiency, 23,48 -50 and advanced age 25,49,[51][52][53] have been reported to potentiate bleeding during warfarin therapy and are highly prevalent in the dialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…2 the US Renal Data System reported a 10-fold increase in subdural hemorrhages in dialysis patients (although their medication was not specified) when compared with nondialysis patients, 43 whereas a review of 28 studies of warfarin use in dialysis patients suggested its use doubled the risk for major bleeding. 44 Treated hypertension, 18 -20,45,46 cerebrovascular disease, 23 ischemic stroke, 21,47 serious heart disease, 23 renal insufficiency, 23,48 -50 and advanced age 25,49,[51][52][53] have been reported to potentiate bleeding during warfarin therapy and are highly prevalent in the dialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…Higher risk of gastrointestinal bleeding and subdural hematomas in this population have been described previously. 21,22 Defects in coagulation pathway and use of anticoagulation in dialysis are thought to contribute toward this increased risk of bleeding in patients on maintenance dialysis. We found the incidence of SAH hospitalizations to be higher in females and blacks irrespective of need for maintenance dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier Japanese study found that acute SDH accounts for 8.6% of sudden deaths in patients receiving dialysis (11). Sood et al reported that the risk of nontraumatic SDH in long-term hemodialysis (HD) patients is 10-fold higher than that of the general United States population (10). We recently found that HD-treated patients with ESRD were at nearly 4 times higher risk of SDH than study participants without kidney disease (12).…”
Section: Introductionmentioning
confidence: 82%
“…Neurologic complications are important causes of morbidity and mortality in patients with ESRD (8). Studies also show that patients with ESRD are at higher risk of developing SDH (9)(10)(11)(12)). An earlier Japanese study found that acute SDH accounts for 8.6% of sudden deaths in patients receiving dialysis (11).…”
Section: Introductionmentioning
confidence: 99%